2004
DOI: 10.1256/qj.02.156
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐stratospheric Rossby wave trains in the southern hemisphere: A case‐study for late winter of 1997

Abstract: SUMMARYBehaviour of quasi-stationary circulation anomalies observed in the lower stratosphere of the extratropical southern hemisphere during austral late winter of 1997 is studied. The anomalies are de ned as daily low-passltered departures from the circulation varying slowly with the seasonal cycle. A wave-activity ux and refractive index for stationary Rossby waves are utilized in the analysis, each of which is de ned locally for the zonally varying westerlies. Subseasonal uctuations in the lower stratosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This important point, which can easily be seen from the extended CD, could not be gleaned from the case-studies of either Canziani and Legnani (2003) or Nishii and Nakamura (2004), both of whom confirmed the existence of preferred longitudes for the local vertical propagation of wave activity in zonally non-uniform flow.…”
Section: Ray Tracingmentioning
confidence: 93%
See 1 more Smart Citation
“…This important point, which can easily be seen from the extended CD, could not be gleaned from the case-studies of either Canziani and Legnani (2003) or Nishii and Nakamura (2004), both of whom confirmed the existence of preferred longitudes for the local vertical propagation of wave activity in zonally non-uniform flow.…”
Section: Ray Tracingmentioning
confidence: 93%
“…A more complete picture requires consideration of both the zonal and meridional wind components of the background flow. Nishii and Nakamura (2004) applied a (local) threedimensional refractive index and a wave activity flux vector, both of which hinge on a local coordinate rotation and the assumption of a weakly forced, slowly varying background flow, to examine the vertical propagation of sub-monthly wave anomalies during the 1997 Southern Hemisphere winter. They found that the localized, vertically propagating wave activity that originated in the troposphere and penetrated into the lower stratosphere was sensitive to the three-dimensional structure of the local vertical waveguide and the location of the wave source within the waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…While wave-mean flow interaction is usually small in the SH winter (Thompson and Wallace 2000), there are a few notable exceptions. In 1997, the stratospheric polar vortex was repeatedly disturbed by waves propagating upward from tropospheric quasi-stationary anomalies including blocking highs (Nishii and Nakamura 2004). In 2002, several wave events originating from the midlatitude troposphere disturbed the winter polar vortex (Newman and Nash 2005), which finally resulted in the prominent split of the Antarctic ozone hole (Varotsos 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nishii and Nakamura (2004b) found that a Rossby wave train propagating upwards from a blocking flow configuration over the South Atlantic contributed to the breakdown of the SH polar vortex in late September 2002 that led to the collapse of the ozone hole. Nishii and Nakamura (2004a; hereafter referred to as NN04) analysed dynamical characteristics of submonthly geopotential height fluctuations observed in the SH lower stratosphere during late winter and early spring of 1997. They showed that those fluctuations were often associated with zonally confined Rossby wave trains that had originated from quasi-stationary tropospheric anomalies.…”
Section: Introductionmentioning
confidence: 99%